Socioeconomic position across the life course and falls among middle- and older-aged adults: protocol for a systematic review - Stéphane Cullati; Anita van Zwieten; Catherine Sherrington; Fiona M Blyth; Saman Khalatbari-Soltani; Marcia R Franco; Frerik Smit (BMJ Open)
Introduction Individuals experiencing disadvantaged socioeconomic positions (SEPs) may be at increased risk of falls during middle and older age, and these impacts of socioeconomic factors may vary according to the duration, timing and sequencing of exposures across the life course. However, there has not been a recent systematic review of this evidence. This study, therefore, aims to synthesise existing knowledge on the association between SEP across the life course and falls within middle- and older-aged adults.Methods and analysis We systematically searched for literature in three academic databases from database inception to 15 March 2024: MEDLINE (Ovid), Embase (Ovid) and PsycInfo (Ovid). The search strategy combined MeSH headings and search terms related to SEP, falls, middle- and older-aged adults and observational studies. Cohort, case-control and cross-sectional studies with mean or median participant age of >40 years, which report on the association between at least one socioeconomic indicator across the life course and one fall outcome and are published in peer-reviewed academic journals were included. No language or geographic restrictions were imposed. Titles and abstracts were screened by one reviewer with 20% of titles and abstracts also screened by a second reviewer. Two reviewers independently screened full texts. Data will be extracted using a standardised Excel template. Using a modified Quality in Prognosis Studies (QUIPS) tool, the risk of bias of included studies will be assessed by one reviewer with 20% of studies also independently appraised by a second reviewer. Meta-analyses will be conducted if sufficient homogeneity between studies permits. Otherwise, a narrative synthesis of results will be undertaken.Ethics and dissemination As this is a review of published literature, no ethics approval is required. Findings will be disseminated through a journal article publication, conference presentations and plain-text summaries for public accessibility.PROSPERO registration number CRD42024534813.